Right to reply: Power and ethics in humanities research: a response to Stolp - Horn, Lyn; Van Niekerk, Anton; Theron, Therina; Swartz, Leslie; Le Grange, Lesley (University of the Free State, 2016)
Abstract not available
Keywords: Academic freedom; Humanities; Power; Ethics; Research; Misconduct; Integrity; Stellenbosch University